The Economic policies Impact on the cement industry in Sudan (2005-2018) - Habeeballah, Abdelbagi Sheikheldeen; Saeed, Ismaeel Ibraheem Omer; Elbashir, Abdelrahman Ali (Journal of Economic, Administrative and Legal Sciences, 2023)
The study aims to evaluate the role of economic policies in cement production and marketing in Sudan during the period from 2005 to 2018.It also aims to analyze the effectiveness and efficiency of the use of raw materials for the cement industry by analyzing the production function of the cement industry and the factors affecting it. Cement is considered one of the most important workshops in the development of the industrial sector as this industry raises the added value of industrial production and helps in increasing the national income. The study shows that there is a statistically significant relationship between cement production and availability of raw materials in huge quantities in Sudan. Therefore, the study uses descriptive analytical method to study the situation of cement factories in Sudan. Thus, the study recommends the necessity of establishing new cement factories in Sudan, especially in light of the abundance of raw material through the collection of sufficient and accurate information and of the size of the demand and future expectations.